2000
DOI: 10.1108/08876040010334565
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of service quality: combining the dimensions

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
243
1
47

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(298 citation statements)
references
References 34 publications
7
243
1
47
Order By: Relevance
“…One of the main factors influencing expectations is the consumers' prior knowledge and experience with the product or service on offer (Carman, 1990). Many consumers have prior knowledge of the film industry when watching trailers, such as of actors, directors, film studios and writers; however this is not necessarily the case for all consumers.…”
Section: Consumer Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main factors influencing expectations is the consumers' prior knowledge and experience with the product or service on offer (Carman, 1990). Many consumers have prior knowledge of the film industry when watching trailers, such as of actors, directors, film studios and writers; however this is not necessarily the case for all consumers.…”
Section: Consumer Expectationsmentioning
confidence: 99%
“…All results of the interviews were transcribed and pseudonyms used to replace students' real names. Carman (1990) and Celsi and Olson (1988) show that the participants have high levels of knowledge of actors, thus previous experience is important; however, they have low levels of knowledge of directors and writers, thus perceptual judgements of the trailers is of key concern.…”
mentioning
confidence: 99%
“…Researchers also agree about the fact that technical quality significantly affects customer perceptions of overall service quality (Carman, 2000, Grönroos 1982, 1984, 1990, Rust and Oliver 1994. Grönroos (1984, p. 38) defines this factor as "what remains to the customer when the service process has been completed".…”
Section: Functional and Technical Service Qualitymentioning
confidence: 99%
“…First, using patient perceptions to evaluate the health-care system is becoming common and can be sensitive to discerning differences and deficits in the quality of care that patients receive. [35][36][37] Second, this research identifies how the factors of weight as well as gender influence patients' ability to detect physician bias. Across a number of studies, weight has been identified as an area of greater concern for female than male adolescents, college students, and adults.…”
Section: Introductionmentioning
confidence: 99%